The Gene Encoding Subunit A of the Vacuolar H+-ATPase From Cotton Plays an Important Role in Conferring Tolerance to Water Deficit - Liu, Na; Ni, Zhiyong; Zhang, Haiyan; Chen, Quanjia; Gao, Wenwei; Cai, Yongsheng; Li, Mengyu; Sun, Guoqing; Qu, Yan-ying (Frontiers in Plant Science, 2018)
In plant cells, vacuolar H+-ATPases (V-ATPases) are responsible for deacidification of the cytosol and energisation of the secondary transport processes across the tonoplast. A number of V-ATPase subunit genes have been demonstrated to be involved in the regulation of the plant response to water deficit. However, there are no reports on the role of V-ATPase subunit A (VHA-A) in dehydration tolerance of cotton. In this study, cotton GhVHA-A gene was functionally characterised, especially with regard to its role in dehydration stress tolerance. Expression analysis showed that GhVHA-A was differentially expressed in various cotton organs and was induced by dehydration, low temperature, high salinity, and abscisic acid treatment in leaves. We also report that GhVHA-A improve dehydration tolerance in transgenic tobacco and cotton. Virus-induced gene silencing of GhVHA-A decreased the tolerance of cotton plantlets to dehydration stress. Silencing GhVHA-A decreased chlorophyll content and antioxidant enzyme activities and increased malondialdehyde (MDA) content in cotton under dehydration stress. However, transgenic tobacco expressing GhVHA-A exhibited enhanced dehydration resistance, resulting in reduced leaf water loss, higher average root length, and lower MDA levels under dehydration stress. Meanwhile, overexpression of GhVHA-A in tobacco conferred water deficit tolerance by enhancing osmotic adjustment (proline) and the activities of the antioxidant enzymes superoxide dismutase and peroxidase, thereby enhancing reactive oxygen species detoxification. These results suggest that GhVHA-A plays an important role in conferring resistance to dehydration stress. Our results have identified GhVHA-A as a candidate gene for improving dehydration tolerance in plants.